Lipid Lowering Effects of Coriandrum Sativum Extract and Endurance Training in Streptozotocin Induced Diabetic Rats - Maryam Lohrasebi; Mohammad Amin Edalat Manesh; Seyed Ali Hosseini; Fatemeh Farkhaie; Omid Reza Salehi; Nasibeh Khazemi; Masod kiani (Islamic Azad University, 2016)
Introduction: Diabetes is a metabolic disease which induces increase in lipid profile. The present research aimed to review the lipid lowering effects of coriandrum sativum extract and endurance training in diabetic rats. Methods: Thirty two diabetic rats were selected and divided into four groups of eight rats (1) coriandrum sativum extract, (2) endurance training, (3) endurance training with coriandrum sativum extract and (4) control. Rats of groups 2 and 3 ran on treadmill four weeks, five sessions per week and 60 minutes per session; also, rats of groups 1 and 3 received four weeks 100 mg/kg coriandrum sativum extract daily. For statistical analysis of data were used K- S and two way ANOVA tests (p≤0.05). Results: Endurance training has significant effect on reduction of LDL, VLDL, TG and Cho of diabetic rats (p≤0.05); Coriandrum sativum has significant effect on reduction of LDL, VLDL, TG and Cho of diabetic rats (p≤0.05); also endurance training with coriandrum sativum has interactional effect on the reduction of LDL, VLDL, TG and Cho and increase of HDL of diabetic rats (p≤0.05). Conclusion: It appears that endurance training increases the lipid lowering effects of coriandrum sativum in diabetic rats.